The Effect Of Financial Distress On Stock Prices With Capital Structure As A Moderating Variable - Sabrina Maharani, Nabila Rizka; Adib, Noval (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
The LQ45 Index comprises companies with large market capitalization and high liquidity on the Indonesia Stock Exchange (IDX), making it a primary benchmark for national stock market performance. However, global economic volatility and domestic pressures can increase the risk of financial distress. This quantitative study aims to analyze the effect of financial distress on the stock prices of companies listed in the LQ45 Index on the IDX during the 2021-2023 period, with capital structure as a moderating variable. Financial distress was measured using the Modified Altman Z-Score model, while capital structure was measured using the Debt-to-Equity Ratio (DER). The sample consists of 22 companies observed over three time periods. Financial reports and stock price data were processed using panel regression with Moderated Regression Analysis (MRA). The results show that high financial distress tends to lower stock prices, and a high capital structure contributes to declining stock prices due to increased financial risk. Moreover, the interaction test reveals that a high capital structure can weaken the effect of financial distress on stock prices. This suggests that an optimally managed capital structure can help companies mitigate the impact of financial pressure. This study offers insights for management in designing funding strategies and for investors in making investment decisions.